1H NMR-Linked Urinary Metabolic Profiling of Niemann-Pick Class C1 (NPC1) Disease: Identification of Potential New Biomarkers using Correlated Component Regression (CCR) and Genetic Algorithm (GA) Analysis Strategies - Ruiz-Rodado, Victor; Marcos Luque-Baena, Rafael; te Vruchte, Danielle; Probert, Fay; H. Lachmann, Robin; J. Hendriksz, Christopher; E. Wraith, James; Imrie, Jackie; Elizondo, David; Sillence, Daniel; Clayton, Peter; M. Platt, Frances; et al. (Current Metabolomics, 2014)
Niemann-Pick Class 1 (NPC1) disease is a rare, debilitating neurodegenerative lysozomal storage disease; however, urinary biomarkers available for it and its prognosis are currently limited. In order to identify and establish such biomarkers, we employed high-resolution 1H NMR analysis coupled to a range of multivariate (MV) analysis approaches, i.e. PLS-DA, RFs and uniquely the cross-validated correlated component regression (CCR) strategy in order to discern differences between the urinary metabolic profiles of 13 untreated NPC1 disease and 47 heterozygous (parental) carrier control participants. Novel computational intelligence techniques (CITs) were also employed for this purpose. These 1H NMR-linked metabolomics analyses revealed significantly elevated urinary excretions of bile acids, branched-chain amino acids (BCAAs) and their intermediates and degradation products [particularly 3-aminoisobutyrate (3-AIB)], glutamine, 3-methylhistidine, creatine, quinolinate, succinate and trimethylamine, together with diminished concentrations of nicotinate, N-methylnicotinamide, N-methyl-2-pyridone-5-carboxamide (2PY), N-methyl-4-pyridone-5-carboxamide (4PY), and especially trigonelline in NPC1 patients. The CCR and GA designs employed both achieved high levels of classification success, the latter at rates of 96-99%. These results provided evidence for disease-mediated imbalances in enzymes involved in bile acid biosynthesis, BCAA degradation and pyrimidine (thymine) catabolism, together with the nicotinate and nicotinamide, and methylamine metabolism pathways. Metabolite set enrichment and pathway topological analyses indicated that the brain, lysosome, liver, endoplasmic reticulum and mitochondria represented key organ, tissue and sub-cellular localisations for this disease process, observations consistent with NPC1 disease pathology. It is proposed that the BCAA and thymine catabolite 3-AIB, and also selected bile acids, may serve as valuable urinary biomarkers for NPC1 disease.
Keywords: genetic algorithms